(untitled) (Baghdad Science Journal, 2019)
Seeds, beans, leaves, fruit peel and seeds of five plants (Ferula assa-foetida, Coffea robusta, Olea europaea, Punica granatum and Vitis vinifera, respectively) were extracted with four solvents (distilled water, 80% methanol, 80% acetone and a mixed solvent that included methanol, ethanol, acetone and n-butanol at proportions 7:1:1:1). Such manipulation yielded 20 extracts, which were phytochemically analyzed for total polyphenols (TP) and flavonoids (TF). The DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity (RSA) and DPP-4 (dipeptidyl peptidase-4) relative inhibition activity (RIA) were also assessed for each extract. The results revealed that mixed solvent extract of V. vinifera seeds showed the highest content of TP (194.8 ± 2.5 mg Gallic acid equivalent/g dry mass), while methanol extract of V. vinifera seeds recorded the highest content of TF (75.9 ± 0.3 mg catechin equivalent/g dry mass). The C. robusta bean aqueous extract was remarkable in scoring the highest DPPH RSA (87.2 ± 1.2%), while O. europaea leaf methanol extract had the highest DPP-4 RIA (86.4 ± 0.8%). In conclusion, the importance of natural products as radical scavengers and DPP-4 inhibitors is encouraged, and such biological effects were dependent on the plant species and the solvent of extraction. C. robusta beans are suggested to have a prominent RSA, while O. europaea leaves are recommended to be a target for investigations involved in the development of anti-T2DM therapies.